La morale du shoot. Responsabiliser les injecteurs de drogues? - Fernandez, Fabrice (Anthropologica, 2014)
In this article, I question the moral economy of health prevention between the values carried by the policy of harm reduction and those of the injecting drug users living in precarious conditions. Based on an ethnographic study con ducted in France in shooting galleries and at drug prevention associations, this article attempts to understand harm reduction policies that try to encourage injection drug users to take re sponsibility for their actions and to examine what the tensions and moral judgments at work around this process signify. I show the modes of appropriation, opposition or resistance of these drug users in the face of the moral economy of prevention.